COMMUNICATIVE COMPETENCE IN ENGLISH LANGUAGE TEACHING - Pulatova, Khilola (Innovative Development in Educational Activities, 2023)
This article is dedicated to provide reader with necessary theoretical background when we defined the key concepts and supported them with references to leading research authorities in the field. The introduction of the term communicative competence briefly commented on possible difficulties which speakers of foreign language may encounter in communication and that brought us to summarizing reasons for why it is important to develop communicative competence in English language learners.